2016
DOI: 10.1002/ange.201600087
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Morphological Diversity in Two Dimensional Crystalline Porous Polymers by Core Planarity Modulation

Abstract: Tw on ew chemically stable triazine-and phenylcore-based crystalline porous polymers (CPPs) have been synthesized using as ingle-step template-free solvothermal route.U nique morphological diversities were observed for these CPPs [2,3-DhaTta (ribbon) and 2,3-DhaTab (hollow sphere)] by simply altering the linker planarity.Adetailed time-dependent study established as ignificant correlation between the molecular level structures of building blocks with the morphology of CPPs.M oreover,aDFT study was done for cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 4 publications
1
35
0
Order By: Relevance
“…The TEM images of the synthesized COF confirmed its hollow nature and sponge‐like surface of tubules. In Figures d–e, the tubule's center appears as a bright area and its outer surface as a dark area‐a basic characteristic feature of a hollow structure; the nanowires on the outer surface were responsible for the formation of the sponge‐like structure . Statistical analysis of the TEM images provided average values for the outer and inner diameters of the tubules of 0.90 and 0.53 μm, respectively.…”
Section: Figurementioning
confidence: 97%
“…The TEM images of the synthesized COF confirmed its hollow nature and sponge‐like surface of tubules. In Figures d–e, the tubule's center appears as a bright area and its outer surface as a dark area‐a basic characteristic feature of a hollow structure; the nanowires on the outer surface were responsible for the formation of the sponge‐like structure . Statistical analysis of the TEM images provided average values for the outer and inner diameters of the tubules of 0.90 and 0.53 μm, respectively.…”
Section: Figurementioning
confidence: 97%
“…including room temperature FT-IR analysis and solvent stability tests under harsh conditions have been previously reported to characterize interlayer hydrogen bonding in COFs, 12,[17][18][19] direct observation can still be challenging. We expected that the presence of strong hydrogen bonding interactions would lead to significant frequency shifts in IR spectrum of the functional groups directly involved in the hydrogen-bonded bridges.…”
Section: Spectroscopic Studies Of Cofs -Even Though Multiple Experimementioning
confidence: 99%
“…There are only a few examples of hydrazone 17,18 or urea 12 containing COFs where interlayer hydrogen bonding is observed or predicted, reported in literature. Several COFs have been reported that have interlayer C-H⋯O, and C-H⋯N hydrogen bonding through sidechain interactions, 13,14,19 however, more canonical N-H⋯O hydrogen bonding interactions similar to those found between amide groups found in Nature, or in synthetic polymers such as Kevlar or Nylon, are much rarer.…”
mentioning
confidence: 99%
“…Similarly, Banerjee and co-workers constructed flower-like COFs and the sheet-like structures were also prepared by using π-π stacking of COF layers [ 99 ]. They also synthesized hollow spherical COFs (COF-DhaTab) through an Ostwald ripening process, as shown in Figure 8 b [ 116 , 239 ]. The formed COF-DhaTab showed rod-shaped morphology at first and then were aggregated.…”
Section: Developments Of Cofsmentioning
confidence: 99%